2017
DOI: 10.1007/s00787-017-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Separation anxiety among birth-assigned male children in a specialty gender identity service

Abstract: Previous research suggested that separation anxiety disorder (SAD) is overrepresented among birth-assigned male children clinic-referred for gender dysphoria (GD). The present study examined maternally reported separation anxiety of birth-assigned male children assessed in a specialty gender identity service (N = 360). SAD was determined in relation to DSM-III and DSM-IV criteria, respectively. A dimensional metric of separation anxiety was examined in relation to several additional factors: age, ethnicity, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Three cross-sectional studies and one retrospective explicitly addressed the issue of SA: we have already cited the work from Santarossa et al (2019). VanderLaan et al (2018) in a clinical sample of birth-assigned boys found SA significantly more prevalent in the gender-referred group, compared to the estimated US population prevalence; however, when testing the predictive role gender nonconformity along with of socio-demographic characteristics, CBCL Internalizing, Externalizing and poor peer relations scores, gender nonconformity did not significantly predict SA; only CBCL internalizing score, age and parental marital status significantly predicted SA. Thus, the authors concluded that SA could be understood as a problem within the spectrum of internalizing problems for which male children clinic-referred for GD show elevation.…”
Section: Narrative Synthesis Of Resultsmentioning
confidence: 99%
“…Three cross-sectional studies and one retrospective explicitly addressed the issue of SA: we have already cited the work from Santarossa et al (2019). VanderLaan et al (2018) in a clinical sample of birth-assigned boys found SA significantly more prevalent in the gender-referred group, compared to the estimated US population prevalence; however, when testing the predictive role gender nonconformity along with of socio-demographic characteristics, CBCL Internalizing, Externalizing and poor peer relations scores, gender nonconformity did not significantly predict SA; only CBCL internalizing score, age and parental marital status significantly predicted SA. Thus, the authors concluded that SA could be understood as a problem within the spectrum of internalizing problems for which male children clinic-referred for GD show elevation.…”
Section: Narrative Synthesis Of Resultsmentioning
confidence: 99%